Perancangan Aplikasi Kemahasiswaan Berbasis Website pada Kalbis Institute - Joseph Vetry; Poltak Pancarian Situmorang (UNIVERSITAS KALBIS, 2023)
This article will discuss the design of student applications that will be applied to the Kalbis Institute, The purpose of designing student applications is to make students get information related to students easier. This research uses the prototyping method. The model used is integrated modeling language with diagrams used, namely use case diagrams and activity diagrams. And when trying to do testing the wrtitter are using black-box testing. The result of the research is a student application for Kalbis Institute and is expected to make it easier for students to get any information at Kalbis Institute.